Collaborative Governance in Urban Waste Management: Policy Evaluation of Malang City in the Post-Pandemic SDGs Era - gunawan, ari (PANGRIPTA, 2025)
This study examines the dynamics of collaborative governance in the implementation of waste management policy in Malang City, Indonesia. Despite the city’s formal commitment to community-based waste management through Local Regulation No. 7/2021, collaboration remains limited in practice. Using a qualitative case study approach, data were collected through semi-structured interviews, focus group discussions, field observations, and document analysis involving key stakeholders, including government officials, community actors, and informal sector workers. Findings reveal four critical barriers to effective collaboration: (1) asymmetrical power relations that restrict community involvement in policy design; (2) fragmented institutional arrangements with unclear coordination mechanisms; (3) strong bureaucratic control that limits facilitative leadership; and (4) weak participatory processes characterized by symbolic dialogue, low shared understanding, and declining public ownership. These constraints prevent the alignment of policy intentions with on-the-ground realities and hinder the achievement of sustainable development goals (SDGs) and circular economy targets. The study proposes a shift from a policy control model to a policy co-creation approach. Key policy implications include institutionalizing multi-stakeholder forums, formally recognizing informal waste actors, empowering local innovation through facilitative leadership, and building shared digital infrastructure for feedback and monitoring. These reforms are essential for transforming waste governance from symbolic participation into meaningful collaboration. By embedding co-creation into policy practice, Malang City can enhance its environmental performance while promoting inclusive, adaptive, and sustainable urban development.